2013
DOI: 10.1016/j.matbio.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A cytokine axis regulates elastin formation and degradation

Abstract: Underlying the dynamic regulation of tropoelastin expression and elastin formation in development and disease are transcriptional and post-transcriptional mechanisms that have been the focus of much research. Of particular importance is the cytokine–governed elastin regulatory axis in which the pro-elastogenic activities of transforming growth factor β-1 (TGFβ1) and insulin-like growth factor-I (IGF-I) are opposed by anti-elastogenic activities of basic fibroblast growth factor (bFGF/FGF-2), heparin-binding ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 128 publications
1
46
0
Order By: Relevance
“…The proliferative effect on tenocytes and tenoblasts supports the intrinsic healing mechanism, by attracting these cell populations from the endotenon, which in turn can synthesise and remodel the ECM. On the other hand, there is an evidence that the effect of PDGF-BB on elastin synthesis is inhibitory, where the MAPK/ERK signalling pathway acts in opposition to canonical TGFβ1 signalling (Sproul and Argraves, 2013). However, its mechanism and role in tendon healing are yet unknown.…”
Section: Pdgf-bb Is Predominantly Expressed During Tendon Healingmentioning
confidence: 99%
“…The proliferative effect on tenocytes and tenoblasts supports the intrinsic healing mechanism, by attracting these cell populations from the endotenon, which in turn can synthesise and remodel the ECM. On the other hand, there is an evidence that the effect of PDGF-BB on elastin synthesis is inhibitory, where the MAPK/ERK signalling pathway acts in opposition to canonical TGFβ1 signalling (Sproul and Argraves, 2013). However, its mechanism and role in tendon healing are yet unknown.…”
Section: Pdgf-bb Is Predominantly Expressed During Tendon Healingmentioning
confidence: 99%
“…Because the GLP-1R could not be detected in cardiac fibroblasts, we explored the possibility that the elastogenic effect of GLP-1 might be induced through other receptor(s) previously identified to be involved in elastinproducing signaling pathways (22,23,29,30). Results of a series of experiments indicated that treatments with selected inhibitors of the well-established elastogenic pathways, triggered either by TGF␤-1 (SB431542) or insulin (AG1024), as well as treatment with dimethyloxaloylglycine, an inhibitor of proline hydroxylase that blocks collagen fibrogenesis, did not interfere with the elastogenic effect of GLP-1 peptides (data not shown).…”
Section: Glp-1 (7-36) and Glp-1 (9-36) Stimulate Elastinencoding Mrnamentioning
confidence: 99%
“…After confirming that the known GLP-1R is not expressed in cardiac fibroblasts (Figure 2), we considered the involvement of alternate pathways involved in elastic fibers deposition (30). Although GLP-1 had been previously documented to engage its own receptor to trigger either the IGF-IR-dependent protection against apoptosis (51), or the EGF-1-dependent proliferative signals in pancreatic ␤-cells (52), here, we provide the first experimental evidence that GLP-1 can also cross-activate the IGF-IR in cardiac fibroblasts lacking the known GLP-1R.…”
mentioning
confidence: 92%
“…Furthermore, because MMP2 and MMP9 expression increased after TNF-a stimulation of epithelial cells, and because MMPs were recently associated with the breakdown of elastin in SPC-TNF-a mice and patients with COPD, TNF-a could possibly contribute to the reported degradation of elastin (3,23). This is supported by evidence of research that shows that suppression of tropoelastin in TNF-a stimulated fibroblasts directly, and breakdown of elastin through increased release of elastolytic enzymes (9). In addition, a role for TNF-a in tissue remodeling is evident from a study demonstrating protection of TNF-a receptor knockout mice to cigarette smoke-induced connective tissue breakdown (10).…”
Section: Discussionmentioning
confidence: 90%
“…A role for TNF-a in tissue remodeling is further evident from a study that demonstrated that TNF-a receptor knockout mice were protected from cigarette smoke-induced connective tissue breakdown (9,10). In addition, it was recently shown that, in alveolar epithelial cells, TNF-a can induce JNK signaling (11) and that JNK is involved in TNFa-induced MMP12 expression (12).…”
Section: Clinical Relevancementioning
confidence: 99%